2016
DOI: 10.1007/s00253-015-7265-y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of antifungal activity of antimicrobial peptide APP, a cell-penetrating peptide derivative, against Candida albicans: intracellular DNA binding and cell cycle arrest

Abstract: We investigated the antifungal properties and anti-candidal mechanism of antimicrobial peptide APP. The minimum inhibitory concentration of APP was 8 μM against Candida albicans and Aspeogillus flavus, the concentration against Saccharomyces cerevisiae and Cryptococcus neoformans was 16 μM, while 32 μM inhibited Aspergilla niger and Trichopyton rubrum. APP caused slight depolarization (12.32 ± 0.87%) of the membrane potential of intact C. albicans cells when it exerted its anti-candidal activity and only cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 30 publications
4
46
0
Order By: Relevance
“…Meanwhile, the increased membrane permeability allows GHc and GHd to enter the cell and bind to DNA, contributing to a decrease in synthesis levels in bacterial DNA. These results are consistent with the findings of Li et al, who observed that the antimicrobial peptide APP damaged bacterial membrane permeability and bound to bacterial DNA to influence intracellular life activity (Li et al, 2016). According to the literature, AMPs could be used to inhibit the formation of biofilms and to eradicate mature biofilms (Mishra and Wang, 2017;Verly et al, 2017).…”
supporting
confidence: 91%
“…Meanwhile, the increased membrane permeability allows GHc and GHd to enter the cell and bind to DNA, contributing to a decrease in synthesis levels in bacterial DNA. These results are consistent with the findings of Li et al, who observed that the antimicrobial peptide APP damaged bacterial membrane permeability and bound to bacterial DNA to influence intracellular life activity (Li et al, 2016). According to the literature, AMPs could be used to inhibit the formation of biofilms and to eradicate mature biofilms (Mishra and Wang, 2017;Verly et al, 2017).…”
supporting
confidence: 91%
“…Membrane disruption can be further characterized by measuring which components leak out of bacterial cells, i.e., ions, ATP, or DNA/RNA. For example, cellular ions, phosphorus, and sulfur can be detected by atomic emission spectroscopy after exposing bacterial cells to HDPs (Wenzel et al, 2014(Wenzel et al, , 2015Li et al, 2016). For select ions, such as potassium, leakage can also be determined using a selective electrode (Tsutsumi et al, 2012;Wenzel et al, 2012;Hou et al, 2019).…”
Section: Leakage Of Intracellular Componentsmentioning
confidence: 99%
“…Therefore, in addition to determining antibacterial activities, we measured the in vitro antifungal properties of PMAP-36 and its derivatives against Candida in the present study. C. albicans is a common opportunistic high-infective fungus and was used as a reference fungal strain to investigate the antifungal mechanism of AMPs against Candida 192021.…”
mentioning
confidence: 99%